The Impact of Problem-Based Learning Model with Focus Group Discussion Method on Students’ Learning Outcomes in Basic Vocational Subjects - Safitri Agustin; Hanesman; Efrizon; Hendra Hidayat (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This study aims to evaluate the effect of the problem-based learning (PBL) model with the focus group discussion (FGD) method on students’ learning outcomes in the basic vocational subjects at SMK Negeri 1 Sumatera Barat. We employed a quasi-experimental research method, utilizing two sample groups: the experimental group (class X E2), which implemented the PBL model with the FGD method, and the control group (class X E1), which received direct instruction. We collected learning outcome data through pretest and posttest assessments and analyzed the mean differences between the two groups using a t-test. The study’s results revealed a significant improvement in students’ learning outcomes in the experimental group, with a mean posttest score of 87.48, compared to the control group, which scored 78.48. The hypothesis test showed a significant difference between the two groups, with a calculated t-value (4.086) exceeding the critical t-value (1.66). This indicates that the implementation of the PBL model with the FGD method has a positive influence on students’ learning outcomes. These findings underscore the potential of the PBL model as an effective instructional strategy for enhancing students’ learning outcomes and provide a foundation for further developments in education.